Sistematización del proceso histórico de la conformación de la psicología en Ecuador a realizarse durante los meses de mayo a octubre de 2015 - Camacho Proaño, Diego Francisco (2016)
The History of Psychology in Ecuador has been an elusive topic for the psychological community in the country, and has become a problem to be addressed in these times of change of educational reforms and adaptations to search for relevance and social, political and cultural recognition for psychology in Ecuador, and it certainly is a process that must be carried out based on research of qualitative type, which allow you to have a clear plain of the historical situation of psychology, of how certain processes have been changing and influencing the students and professional practitioners of psychology in the country. This study aims to be a starting point and a source of projection of new studies, which may contribute to the construction of this historical process that is nonexistent in our country, and should be taken seriously by the universities with areas of psychology ; since it is ironic, that a science that works with historical accounts from the subjectivity of people and that seeks to organize to safeguard mental health, does not have its own historical record, where they can rethink national psychology for the better organization and recognition that a science of this magnitude should have.